The anthropology of argument - Tindale, Christopher W. (Christopher William), author.
1 online resource
Keywords: "This innovative text reinvigorates argumentation studies by exploring the experience of argument across cultures, elucidating the significance of the anthropological turn in the domains of rhetoric, communication, and philosophy. The Anthropology of Argument fills an important gap in contemporary argumentation theory by shifting the focus away from the purely propositional element of arguments and onto how they emerge from the experiences of peoples with diverse backgrounds, demonstrating how argumentation can be understood as a means of expression and a gathering place of ideas and styles. Confronting the limitations of the Western tradition of logic and searching out the argumentative roles of place, orality, myth, narrative, and audience, it examines the nature of multi-modal argumentation. Tindale analyzes the impacts of colonialism on the field and addresses both optimistic and cynical assessments of contextual difference. The results have implications for our understanding of contemporary argumentative discourse in areas marked by deep disagreement, like politics, law and social policy. The book will interest scholars and upper-level students in communication, philosophy, argumentation theory, anthropology, rhetoric, linguistics, and cultural studies"--